The Impact of Myocardial Bridging on the Coronary Functional Test in Patients with Ischaemia with Non-Obstructive Coronary Artery Disease - Hiroki Teragawa; Chikage Oshita; Yuko Uchimura (Life, 2022)
Background: The possibility of myocardial bridging (MB) causing chest pain has been widely reported; however, the effect of MB on coronary microvessels has not been thoroughly investigated. Therefore, this study evaluated the effects of MB on epicardial coronary artery and coronary microvascular function during coronary angiography (CAG) and coronary function test (CFT) in patients with ischaemia with non-obstructive coronary artery disease (INOCA). Methods: This study included 62 patients with INOCA who underwent CAG and CFT for the left anterior descending coronary artery (LAD) to evaluate chest pain. In the CFT, acetylcholine was first administered intracoronarily in a stepwise manner, followed by chest symptoms, electrocardiographic ST-T changes and CAG. Positive coronary spasm was defined as coronary vasoconstriction of >90% on CAG accompanied by chest symptoms or electrocardiographic ST-T changes. After nitroglycerin administration, CAG was performed to assess MB, which was defined as systolic narrowing of the coronary artery diameter by >20% compared with that in diastole. Coronary flow reserve (CFR) and index of microcirculatory resistance (IMR) were subsequently obtained via transvenous adenosine triphosphate infusion using a pressure wire. Coronary microvascular vasodilatory dysfunction (CMD) was defined as a CFR of <2.0 or an IMR of ≥25 units. Results: Of the 62 patients, 15 (24%) had MB. The patients’ characteristics did not differ between the two groups. Regarding the CAG and CFT results, the presence of coronary spasm in the LAD was higher in the MB (+) group (87%) than in the MB (−) group (53%, p = 0.02), whereas the values of CFR (MB (+): 2.7 ± 1.4, MB (−): 2.8 ± 1.1) and IMR (MB (+): 26.9 ± 1.0, MB (−): 30.0 ± 17.3) and the presence of CMD (MB (+): 53%, MB (−): 60%) were similar in the two groups. Conclusions: The findings suggest that MB predisposes patients with INOCA to coronary spasms. Conversely, MBs may have a limited effect on microvessels, particularly in such patients.